2022
DOI: 10.18805/ijare.af-689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulching on Growth and Yield of Peanut (Arachis hypogaea L.) on the Coastal Sandy Land in Nghe An Province, Vietnam

Abstract: Background: Peanut (Arachis hypogaea L.) is one of the oil and cash crops in Vietnam. However, owing to the lack of appropriate management practices, the production and the area under cultivation of peanut have remained low. Mulches are the key factors contributing to promoting crop development and early harvest and increasing yields. Methods: The experiment consisted of three mulch treatments, viz., plastic mulch, straw mulch and no-mulch control. All the treatments were replicated thrice in a complete random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
5
3
0
Order By: Relevance
“…However, the differences between the mulching types and the control were not statistically significant. This observation is also similar to the results of Tran et al (2022).…”
Section: Effect Of Mulching Materials On the Yield Components And Yie...supporting
confidence: 92%
See 4 more Smart Citations
“…However, the differences between the mulching types and the control were not statistically significant. This observation is also similar to the results of Tran et al (2022).…”
Section: Effect Of Mulching Materials On the Yield Components And Yie...supporting
confidence: 92%
“…The highest dry matter was recorded for clear plastic (45.91 g/plant), followed by rice straw (44.61 g/plant), while lesser values were found for sugar cane bagasse (43.99 g/plant) and water hyacinth (43.83 g/plant). This is in line with several studies that found the growth characteristics of peanuts were highest under polythene mulching, followed by rice straw mulching (Dutta, 2006;Jain et al, 2018;Tran et al, 2022).…”
Section: Effects Of Mulching Materials On the Leaf Area (Lai) And Dry...supporting
confidence: 91%
See 3 more Smart Citations